SEMANTIC ERRORS IN THE TRANSLATION OF THE HINDU’S INSTAGRAM ACCOUNT (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2021)
This research is mainly aimed at analyzing the semantic error in lexis occurred in the translation done by Instagram machine translation. This research objective is to find out the types of semantic error in lexis done by the machine translation. Observation method used as method of collecting the data. The analysis applied descriptive qualitative method in analyzing the data which were taken from the posts in The Hindu’s Instagram account. This account has been verified by Instagram as an official accountthat sharing news on India and it has more than 1.7 million followers currently. The theory from James (1998) was utilized to analyze the types of semantic error data source. In early stages of observation has found the phenomenon in the product of translation done by the Instagram machine translation. There was confusion of sense relation and collocation error in choosing a wrong synonym. Moreover, there was also several of translation procedures used in translating the Instagram captions of The Hindu.